Negative Hook Storytelling: A study on the impact of Instagram influencer advertisements among Gen Z - Habeeb Ur Rahaman.S; Ms.Gaythri C.S (Asosiasi Dosen Muda Indonesia, 2026)
The growth of digital technologies and social media has made enormous developments in the field of online advertising. The social media advertisements are more effective in promoting the products than the traditional methods. The use of social media platforms and targeting the consumers of a particular category is useful to all promoters to make their product promotion in an effective way. Instagram influencers are helpful in creating a live human experience about a product and its usage. Negative hook is a technique for seeking the attention of viewers and making them watch the full advertisement video without scrolling down. The negative hook technique will have negative information about the product or its usage in the beginning of the video followed by the actual real information which will make the people watch the full video. The viewers are more engaged with storytelling concepts of Instagram advertisements (Madiha Atiq 2022). This study aims to focus on the impact of Instagram influencers advertising through negative hook storytelling and how gen Z are attracted towards the promotion videos. The study will be conducted using a quantitative research method. The Gen Z viewers from Chennai, Tamil Nadu will be selected as research samples. Survey research tools will be used for collecting data. The study will provide the reach and impact of influencers advertisement and how Gen Z attracted towards the same through negative hook storytelling.